Metabolic signatures of cholesterol biosynthesis and absorption in patients with coronary artery disease. Issue 212 (September 2021) - Kwon, Go Eun; Hyun, Myung Han; Byun, Dong Jun; Paeng, Ki-Jung; Seo, Hong Seog; Choi, Man Ho
Highlights: Lipid profiles and serum levels of free sterols were evaluated for 105 patients who underwent cardiovascular intervention. Upstream precursors of cholesterol revealed atherosclerotic events and metabolic disturbance induced by statin. Metabolic ratios of individual dietary sterols to cholesterol reflected statin response. Metabolic signatures of cholesterol precursors and dietary sterols could be used to understand atherosclerosis and response against statin treatment. Abstract: Due to the biochemical importance of cholesterol homeostasis in cardiovascular disease (CVD), this study was aimed to identify metabolic signatures of serum sterols according to atherosclerotic CVD severity. Biogically active free cholesterol and its 11 analogues in serum samples obtained from subjects who underwent cardiovascular intervention were quantitatively evaluated by gas chromatography-mass spectrometry (GCMS). Study groups were divided by 29 patients with stable angina (SA), 35 patients with acute coronary syndrome (ACS), and 41 controls. In all subjects, serum levels of cholesterol and its upstream precursors of 7-dehydrocholesterol, lathosterol, and lanosterol were closely associated with CVD risk factors, such as total cholesterol, low-density lipoprotein cholesterol (LDL-C), and LDL-C/high-density lipoprotein cholesterol (HDL-C) ratio ( r = 0.407 ∼ 0.684, P < 0.03 for all). Metabolic ratios of lathosterol/cholesterol (control = 55.75 ± 34.34, SA = 51.04 ± 34.93, ACS = 36.52 ± 22.00; P < 0.03) and lanosterol/cholesterol (control = 12.27 ± 7.43, SA = 10.97 ± 9.13, ACS = 8.01 ± 5.82; P < 0.03), were remarkably decreased. Both metabolic ratios and individual concentrations of lathosterol and lanosterol were also decreased in subjects with statin treatment than those in the control group without statin treatment ( P < 0.05 for all), whereas three metabolic ratios of dietary sterols (sitosterol, campesterol, and stigmasterol) to free cholesterol were increased after statin therapy ( P < 0.05 for all) in both SA and ACS groups. The present metabolic signatures suggest that both lathosterol/cholesterol and lanosterol/cholesterol ratios corresponding to cholesterol biosynthesis may reflect statin response. Individual dietary sterols to cholesterol ratios resulted in higher intestinal cholesterol absorption after statin therapy.